2020
DOI: 10.3390/s20061666
|View full text |Cite
|
Sign up to set email alerts
|

Timing and Modulation of Activity in the Lower Limb Muscles During Indoor Rowing: What Are the Key Muscles to Target in FES-Rowing Protocols?

Abstract: The transcutaneous stimulation of lower limb muscles during indoor rowing (FES Rowing) has led to a new sport and recreation and significantly increased health benefits in paraplegia. Stimulation is often delivered to quadriceps and hamstrings; this muscle selection seems based on intuition and not biomechanics and is likely suboptimal. Here, we sample surface EMGs from 20 elite rowers to assess which, when, and how muscles are activated during indoor rowing. From EMG amplitude we specifically quantified the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 41 publications
(69 reference statements)
0
4
0
Order By: Relevance
“…The findings of our study confirmed that VL activation began consistently before the individuals reached the anterior-most seat position. Previous studies on FES-rowing with manual control switching relied mainly on the absolute seat position reaching the anterior-most position [8,9,12]. However, our results demonstrated that only analyzing absolute seat position may be insufficient in determining whether the targeted muscles are stimulated at the optimal time.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…The findings of our study confirmed that VL activation began consistently before the individuals reached the anterior-most seat position. Previous studies on FES-rowing with manual control switching relied mainly on the absolute seat position reaching the anterior-most position [8,9,12]. However, our results demonstrated that only analyzing absolute seat position may be insufficient in determining whether the targeted muscles are stimulated at the optimal time.…”
Section: Discussionmentioning
confidence: 60%
“…Similarly, in a study by Vieira et al (2020) regarding lower limb muscle activation during indoor rowing, all parts of the quadriceps muscle were found to be recruited before the initiation of the drive phase to act as a braking mechanism and decelerate knee flexion at the end of a rowing cycle [12]. However, in the aforementioned study, consistency in the timing of muscle activation was not discussed among muscles [12]. In our study, calculation of a kinematic event (seat position) at the time of muscle activation showed that the VL can be an appropriate muscle to navigate the switch timing in the coaching system.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations